Some New ‘Short Games’ Within a Set of Tennis - Pollard G.; Barnett T. (International Journal of Computer Science in Sport)
Recently there has been an interest in developing tennis scoring systems that involve playing a fewer number of points on average. In devising such ‘shorter’ tennis scoring systems, it would be ideal for them to also have the following four characteristics: A smaller standard deviation of duration, a similar value for the probability that the better player wins, an increased efficiency, and a greater average excitement per point played. Thus, in total there are five considerations when devising such new scoring systems. Quite often in this type of study a scoring system that is ‘better’ with regard to one of these characteristics is ‘worse’ with regard to another (or others). In this paper we outline some new tennis scoring systems that have improvements in all (or almost all) of these five characteristics. We identify 3 or 4 different game structures that could be useful for tournaments. A common thread in the approach taken is the elimination of unimportant and unexciting points within the game structure. The choice of which is the most appropriate new format for a particular tournament would depend amongst other things on the planned reduction in the expected set duration